Formalism and autonomy in the history of art - Fernández Uribe, Carlos Arturo (Estudios de Filosofía, 2000)
From the middle of the nineteenth century, Formalism proposed the principle of artistic autonomy in an attempt to develop the History of Art as a scientific discipline, rejecting the historiography of art subordinated to universal philosophical systems. The ultimate expression of the Formalist methods is found in the concepts elaborated by Wolfflin and in the way he explains the movement from Renaissance to Baroque. Formalist ideas deeply influenced the development of Vanguards and their interest on the artistic form. Yet, those ideas also played a role in the crisis of the whole Modernism. In last decades, new perspectives have appeared that aim at bringing back their achievements for the sake of the discipline of History of Art and the criticism.